Assessing youth labour market services: young people’s perceptions and evaluations of service delivery in Germany - Shore, Jennifer; Tosun, Jale (Public policy and administration, 2019)
While youth unemployment is a widely studied topic, many accounts fail to take into consideration young adults’ experiences with and perceptions of the public services they make use of. Young people’s perceptions of the services they use are closely linked to a variety of behaviours such as noncompliance, early withdrawal or non-take-up, all of which can hinder the (re-)entry to the labour market. How young people evaluate their interactions with employment services can even have impacts on societal and political attitudes; as for many young people, these experiences represent their first interactions with the state. In this study, we draw on unique survey data to offer insights into young adults’ evaluations and experiences with public employment services in Germany and discuss them in light of the structure and organizational capacity of public employment services to deliver the programmes and services that young adults need. By placing the analytical focus on young people’s evaluations, we argue that although Germany is often highlighted as a highly successful case in terms of youth labour market outcomes; there is nevertheless ample room for improvement in terms of how young people assess the offerings and personal experiences with public employment services.